An outbreak investigation of paediatric severe acute respiratory infections requiring admission to intensive care units - Fiji, May 2016 - Julie Collins; Viema Biaukula; Daniel Faktaufon; James Flint; Sam Fullman; Katri Jalava; Jimaima Kailawadoko; Angela Merianos; Eric Nilles; Katrina Roper; Meru Sheel; Mike Kama (World Health Organization Regional Office for the Western Pacific, 2018)
Introduction: Influenza-associated severe acute respiratory infections (SARI) are a major contributor to global morbidity and mortality. In response to a cluster of SARI cases and deaths in pregnant women, with two deceased cases testing positive for influenza A(H1N1)pdm09, an investigation was initiated to determine whether there was an increase of paediatric SARI cases admitted to divisional hospital intensive care units in Fiji in may 2016 compared to May 2013-2015. Methods: Retrospective case finding was conducted at the paediatric intensive care units (PICUs) in Fiji's three divisional hospitals. Data were collected from 1 January 2013 to 26 May 2016. Cases were identified using a list of clinical diagnoses compatible with SARI. Results: A total of 632 cases of paediatric SARI with complete details were identified. The median age of cases was 6 months (Interquartile range: 2-14 months). Children aged less than 5 years had a higher rate of paediatric SARI requiring admission to a divisional hospital PICU in May 2016 compared to May 2013-2015 (Incidence rate ratio: 1.7 [95% CI: 1.1-2.6]). This increase was not observed in children aged 5-14 years. The case-fatality ratio was not significantly different in 2016 compared to previous years. Conclusion: The investigation enabled targeted public health response measures, including enhanced SARI surveillance at divisional hospitals and an emergency influenza vaccination campaign in the Northern Division.